Phaleria macrocarpa Fruit Flavonoid Extract on Estrogen Receptor Alpha Expression in Ovariectomized Mice - Wijaya, Dyah Ayu Septika; Sutrisno, Sutrisno; Irwanto, Yahya; Anita, Kenty Wantri (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Menopause signifies the cessation of ovarian function, presenting significant health challenges for women globally. Hormonal shifts during menopause impact various systems, including cardiovascular and reproductive health. Changes in reproductive organs increase susceptibility to health issues, necessitating effective management strategies. This study used a true experimental method with a randomized post-test-only control group design to investigate the potential of Phaleria macrocarpa fruit extract, which contains flavonoids, to modulate Estrogen Receptor Alpha (ERa) expression in menopausal mice. Following ovariectomy (OVX), mice treated with flavonoid showed increased ERa expression, with the highest expression observed at a dose of P2 (7.5 mg/mice/day), approaching those in non-OVX control (K-) with a percentage difference of 29.82%. Compared to the OVX control group (K+), the percentage increase was 2387.74%. Therefore, the P2 dose is considered the optimum dose. Regression analysis revealed a significant correlation of 43.3% between flavonoid dosage and ERa expression (p < 0.05). These findings suggest flavonoids as promising natural Selective Estrogen Receptor Modulators (SERMs) for managing menopausal symptoms and reducing endometrial disease risk with ERa modulation. Further research is needed to elucidate the mechanisms of flavonoids, including molecular pathways such as ligand binding and transcription, interactions with other hormones like progesterone, long-term effects, and potential clinical applications. To initiate clinical trials, the author established the P1 dose (3.75 mg/mice/day), which demonstrated expression levels approaching the effects produced by P2. Overall, flavonoids offer potential therapeutic benefits in addressing menopausal health concerns, with the identified optimal dosage providing valuable guidance for future studies and clinical interventions.